Grading Of Fatty Liver on Ultrasound and Its Correlation with Lipid Profile and Liver Enzymes - Anand K; Amulya Sundari V; Ashok Kumar (Asian Journal of Medical Radiological Research, 2019)
Background: To correlate the grades of fatty liver on ultrasound with degree of alterations in lipid profile and liver enzymes.Subjects and Methods: The prospective, analytical observational studywas conducted at a super specialtyhospital based in south Indiain 122 patients diagnosed with fatty liver.The subjects underwent ultrasonography, and lipid profile and liver enzyme tests as a part of clinical evaluation. Those with positive viral markers and on drugs altering the various biochemical parameters were excluded. A radiologist graded the fatty liver into 3 grades- grade I, II and III using the visual grading system. Statistical analyses were carried outto determine the correlation between the grades of fatty liver and alterations in lipid profile and liver enzymes.Results:Out of the 122 selected participants, 51 subjects were categorizedas grade I, 63 as grade II and 8 as grade III fatty liver. There was statistically significant variation in AST, ALT and GGT among different grades (P value < 0.05).However, no significant variation in the BMI was found among patients with different grades of fatty liver.Conclusion: The increase in serum levels of AST, ALT, and GGT concentrations with the increase in the grades of fatty liver by ultrasonography might be useful in predicting theinflammation and progression of the disease. This preliminary finding may be useful for developing a non-invasive method for early diagnosis and predicting the disease prognosis.